CONSUMER PROTECTION IN THE PERSPECTIVE OF ISLAMIC LAW AND LAW NUMBER 8 OF 1999 - SH, Nurhalis, (Jurnal IUS, 2015)
In Islamic Law, principles of consumer protection has been done since Muhammad SAW was appointed as a Rasul. In Indonesia, there is special law that regulate about consumer protection called Law Number 8 Year 1999 on Consumer Protection. The writer was interested to analyze about âConsumer Protection on the Perspective of Islamic Law and Indonesian Law (Law Number 8 Year 1999)â because of majority of Indonesia citizens are moslems. The problem on this thesis is how the protection to the consumer based on Islamic Law and Law Number 8 Year 1999. After conducting research which used conceptual approach, statute approach and comparative approach and six supporting theories are maqashid al syariâah, mashlahah, legal protection, comparative law, utilitarianism and social responsibility. Writer can concluded that Islamic Law give protection to the consumer in order to create a prosperous society. In giving protection to consumer, Islamic Law and Law Number 8 Year 1999 have many similarities eventough in principle matters there is many differencess, because in giving consumer protection, Islamic Law more emphasis on religiosity value with not put aside of social value, while Law Number 8 Year 1999 more emphasis on social and humanity value. Keywords : Consumer Protection, Islamic Law, Law on Consumer Protection